Über grosse Abweichung für diskreten Zufallsgrößen - Survila, P. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: П. Сурвила. О больших уклонениях в локальной теореме для решетчатых случайных величин P. Survila. Apie didelius nukrypimus lokalinėje teoremoje rėtiniams dydžiams